Deep drawing of fiber metal laminates using an innovative material design and manufacturing process. (February 2021) - Blala, Hamza; Lang, Lihui; Li, Lei; Alexandrov, Sergei
Abstract: Fiber-Metal Laminates (FMLs) have gained increasing attention in the advanced industry due to their unique structural reliability, weight reduction, and improved damage tolerance. Nevertheless, the existing forming approaches are not well qualified for the high-volume manufacturing of small and complex laminate components. With the forming of FMLs, the cured fiber and resin matrix layers are deformed elastically, and the metal layers are deformed plastically. The attainable deformation is depending on the strain amount can endure by the glass fibers and by the strength of the interface among the layers. In current research work at the department of aircraft manufacturing engineering at Beihang University, a promising cost-effective approach for the automated mass production of small parts made of FMLs was proposed using new material design and manufacturing process. The new process combined an optimized inner glass fiber patches and non-cured FMLs, followed by the Hot-pressing. Results were very encouraging and exhibited that FML parts manufactured by using this new preparation and process may pave the way for industrial-scale utilization. Highlights: Importance of optimized FMLs material design and deep drawing process. Forming FMLs in No-cured condition and hot-pressing improved the wall homogeneity. Forming FMLs using multi glass fiber patches enhance the formability.